Channel Coordination Under Price Protection, Midlife Returns, and End-of-Life Returns in Dynamic Markets - Taylor, Terry A. (Management Science, 2001)
This paper examines three channel policies that are used in declining price environments: Price protection (P) is a mechanism under which the manufacturer pays the retailer a credit applying to the retailer's unsold inventory when the wholesale price drops during the life cycle; midlife returns (M) allow the retailer to return units partway through the life cycle at some rebate; and end-of-life returns (E) allow the retailer to return unsold units at the end of the life cycle. Under declining retail prices, if the wholesale prices and the return rebates are set properly, then EM (i.e., midlife and end-of-life returns) achieves channel coordination. However, such a policy may not be implementable because it may require the manufacturer to be worse off as a result of coordination. If P is used in addition to EM and the terms are set properly, then PEM guarantees both coordination and a win-win outcome. If the retail price is constant over time, then EM is sufficient to guarantee both coordination and a win-win outcome.